(3GSJQGJjLjGJ JWhjQ hJMSjf GdCOGA (B:s (3GdCWQ GdefgLjI hGdJWHjbGJ GdYedjI (B/s - (3LGO GdQH, SjO eMeOs ((3GdbGgQI(B: s (3eWHYI GdYTQj(B, s, 2009)
(3jVe EOGQI GdJZjjQ hGdJWhjQ GdJfXjej, YedjGJ EOGQI hJbjje GdCOGA, GSJQGJjLjGJ JOQjH GdehGQO GdHTQjI, EYGOI gfOSI GdYedjGJ, JOQjH hJWhjQ GdehGQO GdHTQjI, JNWjW GdeSGQ GdhXjaj dJWhjQ COGA GdYGedjf, ESJQGJjLjGJ eTGQcI hJecjf GdYGedjf efgL LhOI GdMjGI GdhXjajI, GSJQGJjLjGJ GdJMajR hGdecGaBJ, EOGQI JcfhdhLjG GdeYdheGJ, JWhjQ hJMSjf GdBOGAs
(3HjHdjhZQGajG(B: (3U(B.487s
Keywords: (3EOGQI GdCaQGOs; (3Jbjje GdCOGAs